Do the Monetary Policy Makers Follow Rules? Testing Taylor’s Rule for Nepal - Katuwal, Khagendra (Economic Journal of Nepal, 2019)
The study estimates Taylor’s rule for Nepal by using the annual time series data for the period of 1988-2018. As a requirement of Taylor’s rule, the output gap has been estimated by using Hodric-Perscott filter. Consumer price index has been used as measure of inflation and 91-days treasury bills rate is taken as the proxy for the short-term interest rate set by central bank of Nepal. The ordinary least square method has been used to estimate the Taylor’s equation The results show that. As Augmented Dickey-Fuller test shows that all the variables used in this study are in level form. The results show that there is a positive relationship of T-bills rule with inflation output gap. Interest rate smoothing is found to be a major concern of central bank of Nepal but follows the Taylor’s rule partially.